The Effect of Whistleblowing System Toward Fraud Detection with Forensic Audit and Investigative Audit as Mediating Variable - Priyadi, Andi; Abu Hanifah, Imam; Muchlish, Munawar (Devotion : Journal of Research and Community Service, 2022)
Facing the latest industrial era, the development of the digital economy opens up new possibilities as well as increases the risk of fraud. These changes certainly have a significant impact on the development of accounting. On the other hand, these phenomena and situations have resulted in increasingly fierce business competition, the demands of this competition can change business behavior towards unfair/cheat competition which is a form of economic crime. This study aims to determine the effect of whistleblowing system toward fraud detection with forensic audit and investigative audit as a mediating variable. This study used primary data to obtained important information from the respondents by using purposive sampling method. The object research is 56 auditors in the Inspectorate of Banten Province. Smart PLS 3 was used to analyze the research purpose, that consist are descriptive statistics and hypothesis tested. The result of this study indicates that first, whistleblowing system partially have a positive significant effect on the forensic audit. Second, whistleblowing system partially has a positive significant effect on the investigative audit. Third, whistleblowing system partially has a positive significant effect on the fraud detection. Forth, investigative audit partially have a positive significant effect on the fraud detection. Fifth, forensic audit partially have a positive significant effect on the fraud detection. Therefore, it can be explained that the implementation of a wistleblowing system will encourage and increase employee participation in reporting violations that affect the fraud detection in the organization, with the results obtained from this research.